PENGARUH BIMBINGAN AGAMA ISLAM DALAM MENINGKATKAN PENGENDALIAN DIRI NARAPIDANA PENYALAHGUNAAN NARKOBA DI LEMBAGA PEMASYARAKATAN KELAS IIA PEKANBARU - Rahmad, Rahmad; Karneli, Yeni; Netrawati; Ifdil (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Number abuse drugs Which impact negative on individual behavior and emotions, including control self. Method Which used in study This is analysis quantitative with approach descriptive, where data is collected through questionnaire Which designed to inhabitant built. Data analysis techniques used in study This is analysis regression simple processed​ using SPSS version 25. Population in study This is convict narcotics totaling 855 people and a sample of 58 people. The results of the study This that is based on the t-test obtained mark t count 8.252 > t table 2.003 and the value significance 0.000 < 0.05 and so can concluded that there is influence significant positive​ between Islamic religious guidance in increase control self inhabitant foster narcotics. Based on coefficient test results determination shows an R square of of 0.482 or 48.2%. This proves that the influence of Islamic religious guidance on self-control with a coefficient interval of 0.40-0.599 is included in the moderate category. While the remaining 51.8% is explained by other factors or variables that are not included in this research model.